Eradicating All Rules Through Article 42 of Law 21 of 2023 on The National Capital: A Study of Legal Norms and Morality - Muklis Al'anama; Hendro Prabowo (Simbur Cahaya, 2025)
Legal norms in a regulation are the face of the government in implementing a policy, norms become an important point in the purpose of the law itself, namely justice. Norm ambiguity at least has several aspects, namely: open norms, vague norms, norms that conflict with other norms. All of these aspects are a unity in ‘norm conflict’. Article 42 of Law Number 21 of 2023 on the National Capital City (IKN) explains that, if there are regulations that conflict with the IKN Law, other regulations are considered invalid. Thus, many legal academics have criticised the article as a sweeping article. Thus, this research uses a normative research method that examines the norms and politics of law in Article 42 of the IKN Law using a conceptual approach and a statutory approach. Thus, this research shows that in terms of ratio legis, it is not possible for a law to declare another law invalid, which has an equal status as stipulated in Article 7 of Law Number 12/2011 on the Formation of Legislation